Selfless persons: imagery and thought in Theravāda Buddhism - Collins, Steven (Cambridge University Press, 1982)
This book seeks to explain carefully and sympathetically the Buddhist doctrine of anatta ('not-self'), which denies the existence of any self, soul or enduring essence in man. The author relates this doctrine to its cultural and historical context, particularly to its Brahmanical background, and shows how the Theravada Buddhist tradition has constructed a philosophical and psychological account of personal identity and continuity on the apparently impossible basis of the denial of self.